SOCIALIZATION OF SOIL PROCESSING TECHNIQUES AND AMELIORANTS IN RICE CULTIVATION INNOVATIONS IN THE SRI (System of Rice Intensification) SYSTEM, Binjee Village, Nisam District, North Aceh Regency - Halim Akbar; Muhammad Yusuf; Sakral Hasby Puarada; Umar Husein Abdullah (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
This community service activity aims to enhance the understanding and skills of farmers in Binjee Village, Nisam District, North Aceh Regency, in rice cultivation through the application of soil processing techniques and the production of ameliorants, as well as innovations in the System of Rice Intensification (SRI) rice planting method. The background to this activity is based on the decline in rice productivity due to the narrowing of agricultural land and the lack of adoption of technological innovations by farmers. The implementation method employs a participatory approach, combining material delivery with direct field practice, involving 30 farmers as participants. The activity stages include socialisation, training in soil processing techniques and the production of ameliorants, and demonstrations of innovative SRI planting methods. The results of the activity show that farmers gain new, relevant, and valuable knowledge and demonstrate enthusiasm in implementing the techniques that have been socialised. This activity has a positive impact in raising awareness of the importance of cultivation technology innovation and soil conservation to maintain agricultural productivity amidst the challenges of land conversion.